The Influence Of Organizational Citizenship Behavior (OCB), Communication, And Commitment On Employee Performance At The Department Of Sports And Youth Of Lahat Regency Potential - Rani Anjarsari; Titi Hasanah; Marko Ilpiyanto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyse the influence of Organisational Citizenship Behaviour (OCB), communication, and commitment on employee performanceat the Lahat Regency Youth and Sports Office. Employee performance is considered one of the key factors in achieving organisational goals, especially in the public sector. OCB reflects the voluntary behaviour of employees that goes beyond their fo rmal duties, while effective communication and high commitment are expected to increase work productivity and efficien cy. This study uses a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to 35 respondents who were active employees. Data analysis was performed using multiple linear regression to test the partial and simultaneous effects of independent variables on employee performance. The results showed that OCB, communication, and commitment had a positive and significant effect on employee performance, both partially and simultaneously, indicating the importance of these three factors in improving employeework effectiveness in a public organisation environment.